Pendidikan Kewirausahaan Sosial Berbasis Al-Qur'an - Ahmad Mahfud Arsyad (International Journal of Research, 2023)
The unemployment rate in Indonesia is increasing, especially during the covid-19 pandemic. This unemployment problem has existed before and is difficult to solve because very few Indonesians have the courage to become independent entrepreneurs. Educational background, experience, abilities, business capital and community culture make the courage to become an entrepreneur very low. Islam encourages its followers to become afterlife-oriented entrepreneurs, so that life in this world and the afterlife becomes balanced, therefore social entrepreneurship education based on the Quran is needed. This article examines qualitatively descriptively how social entrepreneurship education based on the Quran can become a concept and idea for entrepreneurship education programs carried out by the government for the community. Social entrepreneurship based on the Quran guides muslims to become accomplished and tough entrepreneurs while still practicing the values ​​of the Quran such as justice, community empowerment and being oriented towards mutual prosperity, not just material gain.